Improved Livingness and Control over Branching in RAFT Polymerization of Acrylates: Could Microflow Synthesis Make the Difference? - Derboven, Pieter; Van Steenberge, Paul H. M.; Vandenbergh, Joke; Reyniers, Marie-Francoise; Junkers, Thomas; D'hooge, Dagmar R.; Marin, Guy B. (Macromolecular rapid communications., 2015)
The superior capabilities of structured microreactors over batch reactors are demonstrated for reversible addition–fragmentation chain transfer (RAFT) solution polymerization of n‐butyl acrylate with the aid of simulations, explicitly accounting for the chain length distribution of all macrospecies types. Since perfect isothermicity can be established in a microreactor, less side products due to backbiting and β‐scission are formed compared to the batch operation in which ineffective heat removal leads to an undesirable temperature spike. For a given RAFT chain transfer agent (CTA), additional microstructural control results under microflow conditions by optimizing the reaction temperature, lowering the dilution degree, or decreasing the initial molar ratio of monomer to RAFT CTA. The superior capabilities of structured microreactors over batch reactors are demonstrated for reversible addition–fragmentation chain transfer solution polymerization of n‐butyl acrylate due to isothermicity of the former. Importantly, detailed kinetic analysis also allows to determine unambiguously the different underlying causes for the effect of the microreactor conditions on the cumulative branching content and the degree of livingness.